Food-derived dipeptidyl-peptidase IV inhibitors as a potential approach for glycemic regulation – Current knowledge and future research considerations. (August 2016) - Lacroix, Isabelle M.E.; Li-Chan, Eunice C.Y.
Abstract: Background: Diabetes, which currently affects 1 in 11 adults, is considered one of the biggest worldwide health crises of the 21st century. Over the last decade, synthetic inhibitors of the enzyme dipeptidyl-peptidase IV (DPP-IV) have emerged as an effective pharmaceutical approach for the management of type 2 diabetes. These molecules exert their beneficial effect by preventing the inactivation of gut-derived hormones that play a pivotal role in glycemic regulation. More recently, food components have been suggested as sources of DPP-IV inhibitors with the potential to help manage blood glucose levels. Scope and approach: This review examines the sources, production, molecular characteristics and modes of action of food-derived DPP-IV inhibitors. Insights into the needs for future research to validate their efficacy and to establish their application in the management of type 2 diabetes are also discussed. Key findings and conclusions: To date, hydrolysates of protein from a variety of food commodities, including both plant and animal sources, have been shown to be able to inhibit the activity of the DPP-IV enzyme. Moreover, a number of peptides, either isolated from these hydrolysates or synthetically produced, as well as non-protein-derived compounds such as polyphenols, have also been identified as DPP-IV inhibitors. These food-derived constituents present different degrees of potency and modes of action on the DPP-IV enzyme. While their effectiveness in humans is currently unknown, findings from in vitro and animal studies conducted to date warrant further research to evaluate their potential as functional food ingredients for glycemic regulation. Highlights: Inhibition of the DPP-IV enzyme is a useful approach for managing type 2 diabetes. Peptides and phenolic compounds have in vitro & in vivo DPP-IV inhibitory activity. DPP-IV inhibitory peptides can be released from proteins by enzymatic hydrolysis. Dietary constituents show a range of potency and mode of action on DPP-IV. Food-derived DPP-IV inhibitors have potential to help regulate blood glucose levels.